Pemberdayaan BUMDes karya bersama melalui optimalisasi limbah domestik sebagai peluang bisnis dan ramah lingkungan di Desa Lombo, Kecamatan Pitu Riase - Inayah, Astrina Nur; Aksan, Muhammad; Muhpidah, Muhpidah; Thahir, Inna Mutmainna Cahyani; Afifah, Nur; Ramadhan, Tri (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2025)
The problems faced by BUMDes Karya Bersama include: (1) Lack of an effective waste management system – there is no proper system for waste collection, sorting, and processing, resulting in waste accumulation or improper disposal; (2) Low public awareness – the village community still lacks understanding of the importance of waste management; (3) Absence of waste-based business innovation – the potential of waste as a business opportunity has not been fully optimized. This activity aims to create new business opportunities based on waste processing that can increase village income, develop an environmentally friendly business model at the village level, and increase scientific knowledge for the community from the service carried out. The method used is counseling and training on how to make banana peel muffins and carrot peel muffins. The partner involved in this activity is BUMDes Karya Bersama. The result of the activity includes improved knowledge and skills, as seen from the active participation of the community in the activity and their engagement in innovating products made from domestik waste. In conclusion, the empowerment of BUMDes Karya Bersama through optimizing domestik waste has created a positive economic and environmental impact, opened up new business opportunities, and raised community awareness of the importance of clean and eco-friendly living. With ongoing support, this initiative has the potential to become an innovative and sustainable village waste management model.